Living the ethics and morality of Islam - Unal, Ali (Somerset, New Jersey : Tughra Books, 2009)
Suitable for those who seek to acquire an accurate knowledge of Islam, this title presents the fundamentals and different aspects of Islamic faith. It makes an effort to peel away the layers of what we think we know about Islam to reveal what Islam says about itself, and to explain the pillars of the Islamic faith
1. Islamic morality -- 2. Humanity: between the highest of the high and the lowest of the low -- 3. Certain virtues encouraged in the Qur'an and the Sunna -- 4. Verses from the Qur'an and a collection of hadiths concerning good, Islamic morals -- 5. The unequalled character of god's messenger
Includes bibliographical references and index
Keywords: Islamic ethics; Islam -- Essence, genius, nature; Religious life -- Islam